2022
DOI: 10.1109/access.2022.3210222
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Combined Collision Detection for Multi-Unmanned Aircraft Systems

Abstract: To mitigate the problem of multiple unmanned aircraft systems (MUAS) conflicts at low altitude and ensure the operational safety, this paper proposes a Multivariate Combined Conflict Detection (MCCD) method for MUAS by combining the characteristics of nominal and probabilistic trajectory method. Firstly, the structural framework of the MCCD method is established based on the concept of potential conflict pool, and a detection pattern is derived for MUAS. Secondly, a three-dimensional conflict fast detection mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The second layer The collision zero model of the UAV and building are generated as described in a existing study [27], and are elliptical and cylindrical shapes, as shown in Equations ( and (2).…”
Section: Problem Formulationmentioning
confidence: 99%
“…The second layer The collision zero model of the UAV and building are generated as described in a existing study [27], and are elliptical and cylindrical shapes, as shown in Equations ( and (2).…”
Section: Problem Formulationmentioning
confidence: 99%
“…A broader review on the use of UAVs is also done in [17], where authors study the challenges and problems that need to be addressed including UAV traffic management and collision avoidance. Several studies have been done with the goal of detecting conflicts by reducing the computation time associated to this complex problem: [18][19][20][21][22]. However, we consider that the problem is not completely solved if thousands of UAVs have to be controlled in real-time, providing enough prediction time to apply deconfliction techniques.…”
Section: Related Workmentioning
confidence: 99%